2005
DOI: 10.1177/1524839904266792
|View full text |Cite
|
Sign up to set email alerts
|

A Review and Synthesis of Research Evidence for Self-Efficacy-Enhancing Interventions for Reducing Chronic Disability: Implications for Health Education Practice (Part II)

Abstract: Chronic diseases such as arthritis, diabetes, and heart disease that cause pain, functional impairment, social and emotional dysfunction, and premature loss of wage earnings constitute a challenging problem for American society. In the absence of any effective cure for these frequently progressive conditions, the secondary prevention of complications, which requires a high degree of communication and cooperation between patient and clinician, and improving quality of life and functional capacity through better… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
370
4
9

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 473 publications
(396 citation statements)
references
References 47 publications
13
370
4
9
Order By: Relevance
“…Three of the empirical studies specifically focused their investigation on the efficacy of the theory being proposed (25)(26)(27) Theories of behaviour change relevant to goal setting practice 9 Self efficacy occupies a central role within social cognitive theory (28)and was a key theoretical construct discussed in thirteen of the retrieved papers (25,(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40). For a review of this theory, see Bandura (1997) (28).…”
Section: Resultsmentioning
confidence: 99%
“…Three of the empirical studies specifically focused their investigation on the efficacy of the theory being proposed (25)(26)(27) Theories of behaviour change relevant to goal setting practice 9 Self efficacy occupies a central role within social cognitive theory (28)and was a key theoretical construct discussed in thirteen of the retrieved papers (25,(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40). For a review of this theory, see Bandura (1997) (28).…”
Section: Resultsmentioning
confidence: 99%
“…42,47,[56][57][58] This is consistent with research in other chronic health conditions, where SE interventions that adopt various strategies such as the use different modes of learning or the involvement of significant others proved to be useful. 136,137 Other studies might have failed to report similar results because of low sample sizes, underpowered analyses or because the interventions were not appropriately targeted (for example, for persons with low self-esteem).…”
Section: Psychological Resources In Sci C Peter Et Almentioning
confidence: 99%
“…Systematic reviews on psychological interventions for asthma found that these methods may be effective, but were inconclusive due to small sample sizes and differing outcome measures (see Smith & Jones, 2015;Yorke et al, 2007). Future studies on interventions should more explicitly incorporate efficacy building and longitudinally measure changes in self-efficacy to further support the importance of self-efficacy for people with asthma, PTSD, and co-morbid disorders (Battersby et al, 2010;Marks et al, 2005;Taylor et al, 2014).…”
Section: Regression Analyses Of Locus Of Control and Self-efficacymentioning
confidence: 99%
“…Previous studies found that high self-efficacy and internal LoC are related to resilience in both mental and physical health outcomes (Strickland, 1978;Strecher et al, 1986;Weiss and Larsen, 1990;Bandura, 1993;Wu et al, 2004;Shelley and Pakenham, 2004;Zajacova et al, 2005;Marks et al, 2005;Cross et al, 2006;Leontopoulou, 2006;Cohen et al, 2008;Waldron et al, 2010;Craig et al, 2011;Oliveira et al, 2012). Specifically in regard to PTSD, self-efficacy and LoC are significantly associated with individual differences in pathology and posttraumatic recovery Heinrichs et al, 2005;Chung et al, 2006Chung et al, , 2007Chung et al, , 2012Jones et al, 2006;Mak et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation